Program KKNT UNA: Ecobrick sebagai Solusi Mengatasi Permasalahan Sampah di Desa Meranti - Paisal Manurung; Bambang Gulyanto; M.Rifaldi Lubis; Nabila Arizka Jauhari Nasution; Giska Indriya; Widya Fitriani (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2026)
The Thematic Community Service Program (KKNT) of Asahan University (UNA) in Meranti Village, themed "Ecobricks as a Solution to the Waste Problem," aims to address the accumulation of plastic waste and raise public awareness of the importance of sustainable waste management. Indonesia currently faces serious challenges in plastic waste management, with the volume increasing and estimated to reach 60 million tons by 2025. Meranti Village, where the majority of residents are farmers, also faces this challenge due to limited waste management facilities and low levels of community participation. Through the UNA KKNT program, students conducted a series of activities including field surveys, community outreach, plastic waste collection, and the creation of ecobricks, which were then assembled into a creative installation, "I LOVE MERANTI." The method used was qualitative with a descriptive-explanatory approach, based on direct observation and literature review. The program results showed that the community was able to collect 10 sacks of plastic waste within two months, which were then processed into high-quality ecobricks. This activity not only provides a practical solution to reducing plastic waste but also increases awareness, skills, creativity, and strengthens village community unity. Thus, ecobricks have proven to be an innovative alternative for managing plastic waste at the village level, with the potential for further development into functional and economically valuable products.